Cutting-Edge Technologies for Inflamed Joints on Chip: How Close Are We? - Kahraman, Emine; Ribeiro, Ricardo; Lamghari, Meriem; Neto, Estrela (Frontiers in Immunology, 2022)
Osteoarthritis (OA) is a painful and disabling musculoskeletal disorder, with a large impact on the global population, resulting in several limitations on daily activities. In OA, inflammation is frequent and mainly controlled through inflammatory cytokines released by immune cells. These outbalanced inflammatory cytokines cause cartilage extracellular matrix (ECM) degradation and possible growth of neuronal fibers into subchondral bone triggering pain. Even though pain is the major symptom of musculoskeletal diseases, there are still no effective treatments to counteract it and the mechanisms behind these pathologies are not fully understood. Thus, there is an urgent need to establish reliable models for assessing the molecular mechanisms and consequently new therapeutic targets. Models have been established to support this research field by providing reliable tools to replicate the joint tissue in vitro. Studies firstly started with simple 2D culture setups, followed by 3D culture focusing mainly on cell-cell interactions to mimic healthy and inflamed cartilage. Cellular approaches were improved by scaffold-based strategies to enhance cell-matrix interactions as well as contribute to developing mechanically more stable in vitro models. The progression of the cartilage tissue engineering would then profit from the integration of 3D bioprinting technologies as these provide 3D constructs with versatile structural arrangements of the 3D constructs. The upgrade of the available tools with dynamic conditions was then achieved using bioreactors and fluid systems. Finally, the organ-on-a-chip encloses all the state of the art on cartilage tissue engineering by incorporation of different microenvironments, cells and stimuli and pave the way to potentially simulate crucial biological, chemical, and mechanical features of arthritic joint. In this review, we describe the several available tools ranging from simple cartilage pellets to complex organ-on-a-chip platforms, including 3D tissue-engineered constructs and bioprinting tools. Moreover, we provide a fruitful discussion on the possible upgrades to enhance the in vitro systems making them more robust regarding the physiological and pathological modelling of the joint tissue/OA.